Outcomes of pregnancy following maternal fontan repair. (18th April 2012) - Stephen, GL; Vause, S; Clarke, B
Abstract : The Fontan procedure is performed in patients with anatomical or functional single ventricle. Modifications have been made to the original procedure, but in essence it involves diverting blood from the right atrium directly to the pulmonary artery. Despite potential complications that can occur after such a repair, an increasing number of these patients are surviving to adulthood. Many of these women may wish to become pregnant. The cardiovascular changes of pregnancy include increase in blood volume, cardiac output, reduced vascular resistance and hypercoagulability of blood. These changes put additional burden on the repair and can potentially cause increased morbidity and mortality for mother and fetus. We report the outcomes of eight pregnancies of women with a Fontan repair who have been managed in a joint obstetric/cardiac clinic in Manchester, U.K. One of these pregnancies unfortunately ended in fetal demise at 18 weeks. Six pregnancies resulted in preterm birth, two spontaneous labours at 31 and 29 weeks. Three were electively delivered at 27, 28 and 31 weeks due to intrauterine growth restriction. One elective delivery was planned at 34 weeks due to recurrent antepartum haemorrhage. There were two episodes of post partum haemorrhage. The outcomes of this small cohort demonstrate high levels of prematurity (6/7), IUGR (3/7) and caesarean section delivery (5/7). The rate of prematurity and growth restriction in this group is higher than has been reported in the literature. Although successful pregnancy in possible in this group of women, it is not without significant risk to fetus and mother.